Straw Composting with Biological Agent Inoculation and Application Biofertilizer to Increase Rice Production - Fitriatin, Betty Natalie; Simarmata, Tualar; Hersanti; Tienturmuktini (International Journal of Sustainable Agricultural Research, 2017)
Problems using straw directly include the contamination of germs on the straw from the previous crop. Alternatives that can be done are giving inoculant of biological decomposers The purpose of the research to test isolates decomposer in the rate of straw decomposition in soil and to test isolates biofertilizer on rice plants in soil treated straw compost. Greenhouse experiment was conducted for selecting isolates and formulations decomposer consortium and biological agents as well as the selection and formulation of biological fertilizers isolates. This experiment was consisted of treatments, i.e. incubation time composting (1, 2, 3, and 4 weeks) and inoculant (formulation A containing microbes T. harzianum, Bacillus subtililis, Cytophaga sp. and Bacillus licheniformis; i2 = Formulation B containing microbes B. subtililis, Cytophaga sp., and B. licheniformis, Streptomyces sp.) The field experiment was conducted to determine the effect of straw compost and biofertilizer inoculants (nitrogen fixation bacteria and phosphate solubilizing bacteria) on rice. Research at this stage using split plot experimental design was repeated three times. The main plot was the doses of straw compost + biofertilizer consisting of 8 treatments (0; 2.5; 5.0; 7.5 t ha-1 without and with biofertilizer 400 g ha-1). The subplot was doses of inorganic fertilizer N, P and K consisting of 5 levels (100%, 90%, 80%, 70% and 60% of recommendations dosages). The results showed that the A formulation containing T. harzianum, B. subtililis, Cytophaga sp. and B. Licheniformis whereas B formulation contains B. subtililis, Cytophaga sp., and B. Licheniformis, Streptomyces sp. B formulation capable of decomposing straw is better than A formulation. Application of straw compost and biofertilizer (5,0 t ha-1 + 400 g ha-1) could increase the yield of rice to 13.3% and substitute 20% of inorganic fertilizer (N, P and K).